Identifying Students' Difficulties in Reading Comprehension Tests - Wardani, Happy Kusuma; Fanny Maulidatus Syukriyah; Bariqotul Hidayah (EJI (English Journal of Indragiri): Studies in Education, Literature, and Linguistics, 2024)
Reading comprehension is a vital skill that students need to develop. However, the reality reveals that students still face difficulties in Reading Comprehension Tests. This study aims to identify the difficulties students encounter in Reading Comprehension tests and the underlying factors contributing to these difficulties. It adopts a qualitative approach and focuses on the 26 tenth graders of MA Ma’arif Miftahul Ulum Melirang as the subjects. To accomplish this, ten types of reading comprehension tests were administered to identify the students’ difficulties in reading comprehension tests. Then, students were provided with questionnaires to elicit their opinions on factors influencing their difficulties in reading comprehension tests. The results revealed that students struggle the most with the Free-Recall test. The Summary test came next as the second most challenging, followed by the gap-filling test, Ordering Tasks, and Editing Test. Additionally, the main scores achieved by students in these five tests fell below the 60-point mark with many students obtaining the lowest scores in them. Therefore, English teachers need to provide effective reading comprehension techniques, focusing on strategies to help students overcome challenges in understanding English texts.